2000
DOI: 10.1055/s-2007-978653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subclinical Hypothyroidism on Body Fluid Compartments

Abstract: In our patients affected with subclinical hypothyroidism, with or without obesity, only obesity appeared related to TBW, ECW and ICW; the subclinical hypothyroidism, on the contrary, had no effect on compartments of body fluids. Bioimpedance is a valid tool to assess body fluid distribution in subclinical hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…In a previous study with patients with hypothyroidism, TBW was found higher in those with hypothyroidism than in patients who were euthyroid 18 . However, similar to our results, Lorenzo et al reported that SH did not affect TBW in adult patients with SH 31 …”
Section: Discussionsupporting
confidence: 89%
“…In a previous study with patients with hypothyroidism, TBW was found higher in those with hypothyroidism than in patients who were euthyroid 18 . However, similar to our results, Lorenzo et al reported that SH did not affect TBW in adult patients with SH 31 …”
Section: Discussionsupporting
confidence: 89%
“…A previous study reported that overt hypothyroid patients had higher body fat, ECW retention and edema, in addition to a relatively unaffected lean body mass component [23]. Another study reported that TBW and ECW in subclinical hypothyroid patients were not altered in body fluid compartments [24]. Our study showed that TSH and free T4 levels did not show a difference according to volume status.…”
Section: Discussionsupporting
confidence: 49%
“…BIA has the advantage of being noninvasive, portable, inexpensive, practical, fast, safe and easy to use and it is widely applied in clinical practice to the assessment of body composition, in terms of evaluation of the nutrition and hydration state [56]. Although it is considered a valid tool to assess body fluid composition and distribution in subclinical hypothyroidism, when compared to dilution methods [57], there are not many studies in the literature concerning the relationship of body composition measured by BIA in thyroid diseases [58]. Most of them are focused on hyperthyroidism [59], on short term hypothyroidism [60] or on subclinical hypothyroidism [57].…”
Section: Discussionmentioning
confidence: 99%